2012
DOI: 10.1254/jphs.12088fp
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal Accumulation in Arterial Walls Causes Vascular Contractile Dysfunction in Spontaneously Hypertensive Rats

Abstract: Abstract. Methylglyoxal (MGO) is a metabolite of glucose and perhaps mediates diabetesrelated macrovascular complications including hypertension. In the present study, we examined if MGO accumulation affects vascular reactivity of isolated mesenteric artery from spontaneously hypertensive rats (SHR). Five-week-old SHR were treated with an MGO scavenger, aminoguanidine (AG), for 5 weeks. AG partially normalized increased blood pressure in SHR. In mesenteric artery from SHR treated with AG, increased accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Because previous reports demonstrated that NO-mediated endothelium-dependent relaxation was impaired in the artery from SHR [6,11,12], this observation may support the idea that the effect of omentin was endothelial NOdependent. However, since our previous results suggested the NO-independent component of vasodilation by omentin in isolated blood vessel [15], we cannot completely exclude the possibility that omentin may reduce the agonists-induced increases in BP via NO-independent mechanisms.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Because previous reports demonstrated that NO-mediated endothelium-dependent relaxation was impaired in the artery from SHR [6,11,12], this observation may support the idea that the effect of omentin was endothelial NOdependent. However, since our previous results suggested the NO-independent component of vasodilation by omentin in isolated blood vessel [15], we cannot completely exclude the possibility that omentin may reduce the agonists-induced increases in BP via NO-independent mechanisms.…”
Section: Discussionsupporting
confidence: 74%
“…Body weight, heart rate (HR), systolic blood pressure (BP) (SBP), mean BP (MBP) and diastolic BP (DBP) represent the average value (Table 1). Noninvasive BP in conscious rats was measured using a tail-cuff method after heating the rats (38°C) (Softron, Tokyo, Japan) [6,11,12]. L-NAME was dissolved in drinking water and given to rats (80 mg/kg, 1 day).…”
mentioning
confidence: 99%
“…[36][37][38][39] To test our hypothesis, we performed vascular functional studies as well as experiments to identify the molecular mechanisms involved. Animals and Experimental Design Male SHR and control WKY were obtained at the age of 4 weeks (Hoshino Laboratory Animals, Inc., Ibaraki, Japan).…”
mentioning
confidence: 99%
“…An important and contributory element in sustained hypertension is an increase in vascular tone, potentially resulting from concurrently reduced relaxation and augmented contraction induced by various endogenous ligands. [19][20][21][22][23][24][25][26] Hypertension-associated vascular dysfunction is partly regulated by endothelium-derived factors. [21][22][23][24] There is a fine balance between endothelium-derived relaxing and contracting factors, a disturbance of this balance can contribute to changes in blood pressure.…”
Section: 18)mentioning
confidence: 99%
“…22,25,[32][33][34] Functional Studies Vascular isometric force was essentially recorded as described in our previous studies. 13,17,22,25,26,28,[32][33][34] Concentration-response curves to ATP (10 for 20 min prior to PE application. To investigate the effect of endothelium on relaxations, we analyzed concentrationresponse curves in the presence/absence of endothelium of superior mesenteric arteries from Wistar rat at 17 weeks of age.…”
Section: 18)mentioning
confidence: 99%